A fetal sheep model for studying compensatory mechanisms in the healthy contralateral kidney after unilateral ureteral obstruction. Issue 6 (December 2015) - Springer, Alexander; Kratochwill, Klaus; Bergmeister, Helga; Csaicsich, Dagmar; Huber, Johann; Mayer, Bernd; Mühlberger, Irmgard; Stahlschmidt, Jens; Subramaniam, Ramnath; Aufricht, Christoph
Summary: Introduction: Fetal unilateral ureteral obstruction (UUO) triggers complex pathophysiology involving not only the affected organ but also the contralateral kidney, which undergoes evident compensatory changes. Objective: We hypothesized that it would be possible to characterize a transcriptomic fingerprint and selected molecular mechanisms for compensatory growth of contralateral kidneys in UUO, specifically focusing on mediators, carriers, membrane transport, and organ crosstalk in an ovine fetal UUO model. Study design: A fetal ovine model of complete UUO was created on the 60th day of gestation. For transcriptomics profiling, total RNA was extracted from vital renal biopsies of contralateral (non-obstructed) kidneys harvested on the 80th day of gestation, and kidneys of untreated fetuses served as controls. Statistical analysis provided the set of differentially regulated genes further forwarded to bioinformatics analysis for identification of eventual compensatory molecular mechanisms. Histological analysis was performed with hematoxylin and eosin and periodic acid–Schiff stains. Results: Contralateral kidneys showed compensatory hypertrophic renal growth, represented on the molecular side by 324 protein coding genes differentially regulated compared with the control kidney samples. Bioinformatics analysis identified an interactome (Figure) consisting of 102 genes with 108 interactions mainly involving transporters (protein transport and protein localization as well as in protein degradation), signaling molecules, DNA/nucleotide/RNA processing, and components of catabolism and cell cycle regulation. Within the interactome, nine receptors were identified as differentially regulated on the contralateral kidney, involving potential renoprotective ligands of the prostaglandin and the bradykinin receptor, arginine vasopressin receptor 1B, and integrin beta 4. Interestingly, a broad range of molecules found differentially expressed, has been previously described in stress response, renoprotection and repair (e.g., MAPK3, MCP1, DICER1, and others). Discussion: The compensatory renal growth interactome provides a network of transcripts significantly altered in the contralateral kidney, potentially allowing novel insights into mechanisms, interactions, and signaling pathways associated with compensatory growth, and renal protection and repair. Interestingly, the finding of an embedded gene signature reflecting signaling and communication suggests a key role of these processes in CRG either by crosstalk, soluble substances, carriers, or membrane signaling. Conclusions: Using a transcriptomics approach, it was possible to identify a gene expression fingerprint of contralateral renal growth in a fetal UUO model. Further studies are warranted to validate those processes and to allow incorporation of this knowledge in new fetal diagnostic or even therapeutic strategies. Figure